2005
DOI: 10.1016/j.molimm.2004.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a porcine UL16 binding protein (ULBP)-like cDNA

Abstract: UL16 binding proteins (ULBPs) are ligands for the NK cell activating receptor NKG2D. A cDNA encoding a porcine ULBP-like protein (PULBP) was cloned and the predicted amino acid sequence exhibited 35-52% identity to human ULBPs. Southern blot analysis suggested that there is only one ULBP-like gene in the pig genome. Transcripts of PULBP and another potential NKG2D ligand, MIC2, were detected by RT-PCR in a wide range of tissues. Recombinant PULBP-Fc and human ULBP2-Fc fusion proteins were made and used to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Using an algorithm to score potential ligands (29), pULBP1 was predicted to bind human NKG2D using both the crystal structure of human NKG2D/human ULBP3 and human NKG2D/mouse Rae-1␤ interactions as template, whereas pMIC2 was predicted to bind NKG2D only using the structure of human NKG2D/human ULBP3 as template (data not shown). Intriguingly, a previous study showed no binding of pULBP1-Fc to the human NK cell line NKL by flow cytometry, whereas binding to porcine PBMC was revealed (33). It was concluded then that pULBP1 does not interact with human NKG2D.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Using an algorithm to score potential ligands (29), pULBP1 was predicted to bind human NKG2D using both the crystal structure of human NKG2D/human ULBP3 and human NKG2D/mouse Rae-1␤ interactions as template, whereas pMIC2 was predicted to bind NKG2D only using the structure of human NKG2D/human ULBP3 as template (data not shown). Intriguingly, a previous study showed no binding of pULBP1-Fc to the human NK cell line NKL by flow cytometry, whereas binding to porcine PBMC was revealed (33). It was concluded then that pULBP1 does not interact with human NKG2D.…”
Section: Discussionmentioning
confidence: 82%
“…Because both pULBP1 and pMIC2 transcripts were detected in a pEC (33), they represent potential ligands for human NKG2D. Therefore, the aim of the present study was to test whether pULBP1 and pMIC2 can act as functional ligands for human NKG2D, resulting in xenogeneic human anti-pig endothelial cell NK cytotoxicity.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, it is conceivable that NCR and NKG2D as well as their ligands have not been subjected to the pressure that caused the evolution of MHC genes and their receptors. The porcine NCR and NKG2D ligands are unknown; however, comparison of porcine and human genomic sequences suggests the presence of one ULBP gene and one MIC-A/MIC-B-like gene (MIC2) in the pig genome (40,41). NKG2D ligands are generally poorly expressed by normal cells but are up-regulated in transformed, infected, and stressed cells in both mice and humans (25).…”
Section: Discussionmentioning
confidence: 99%